Hermeneutics of Al-Ghazzālī Concerning Mercy (al-Raḥmah) and its Social Applications: A Religio-Ethical Study - Dr. Muhammad Ashfaq,; Dr. Shah Junaid Ahmad Hashmi,; Dr. Abdul Ghafar Khan, (Al-Qanṭara, 2024)
This contribution examines the work of Abū Ḥāmid Muḥammad al-Ghazzālī (d.1111) concerning various dimensions of Mercy (al-Raḥmah) in Islam and its applications in our daily life to rectify ourselves participating in the society. It is a significant aspect of Islamic thought to grasp the role of Divine Mercy (DM) in the anthropocosmic entities and its mutual link in the God, Man and Universe Relationship (GMUR). In this qualitative research, we reviewed the theological insight of al-Ghazzālī regarding Divine Mercy (al-Raḥmah al-Ilāhīyyah) and on the other hand, his interpretation about multiple ethical values exercising mercy (al-Raḥmah) at the human level. This work finds that the Islamic concept of mercy is not just an idea and dogmatic perception. It has the practical facets for human attitude and behaviour associated with constructive social input demanded by the Qur’ān and Sunnah. He provided several principles to contextualize making sense of Islamic morality and ethics on a pragmatic scale to enhance and preserve the values for communal amelioration. His contribution shows that with the application of mercy (al-Raḥmah), the relationship with the Prophet Muḥammad (ṣallā llāhu ʿalayhi wa-sallam) should be based upon obedience and spiritual affection, self-purification (heart-cleansing) getting away from any kind of unethical performance and the functions of intellect all are mutually associated. It leads us to think about the framework of Raḥmah-Oriented Society (ROS) in the current global scenario is a supreme need of the Muslim Ummah for the harmonic functions of social matters. It leads us to exercise within the genre of moral par-excellence (makārim al-akhlāq) rooted in Islamic al-Raḥmah Paradigm.